List, który zaginął - Turowski, Andrzej (Artium Quaestiones, 2018)
A Letter That Was Lost Summary The paper presents the history of a letter by Tadeusz Kantor of 1981 that was long lost. Kantor responds in it to a proposal from the Institute of Art History of the University of Poznań to have a series of lectures on the avant-garde. Writing that he had not time for it, he explains in some detail his detachment from the institutional study of the avant-garde at the university, stressing his involvement in the avant-garde activity through his art, in particular the Cricot theater. Kantor insists that the avant-garde does not belong to the public domain, but is a result of the artist’s private experience of anxiety and fear in confrontation with the audience and their emotional response to engaged art.